Preliminary Evidence for Lensing-induced Alignments of High-redshift Galaxies in JWST-CEERS - Viraj Pandya; Abraham Loeb; Elizabeth J. McGrath; Guillermo Barro; Steven L. Finkelstein; Henry C. Ferguson; Norman A. Grogin; Jeyhan S. Kartaltepe; Anton M. Koekemoer; Casey Papovich; Nor Pirzkal; L. Y. Aaron Yung (The Astrophysical Journal)
The majority of low-mass ( ${log}_{10}{M}_{* }/M_{\odot }=9--10$ ) galaxies at high redshift ( z > 1) appear elongated in projection. We use JWST-CEERS observations to explore the role of gravitational lensing in this puzzle. The typical galaxy–galaxy lensing shear γ ∼ 1% is too low to explain the predominance of elongated early galaxies with an ellipticity e ≈ 0.6. However, nonparametric quantile regression with Bayesian Additive Regression Trees (or BART) reveals hints of an excess of tangentially aligned source–lens pairs with γ > 10%. On larger scales, we also find evidence for weak-lensing shear. We rule out the null hypothesis of randomly oriented galaxies at ≳99% significance in multiple NIRCam chips, modules, and pointings. The number of such regions is small and attributable to chance, but coherent alignment patterns suggest otherwise. On the chip scale, the average complex ellipticity 〈 e 〉 ∼ 10% is nonnegligible and beyond the level of our point-spread function (PSF) uncertainties. The shear variance $\langle {\overline{γ }}^{2}\rangle \sim 1{0}^{-3}$ is an order of magnitude above the conventional weak-lensing regime but is more sensitive to PSF systematics, intrinsic alignments, cosmic variance, and other biases. Taking it as an upper limit, the maximum implied “cosmic shear” is only a few percent and cannot explain the elongated shapes of early galaxies. The alignments themselves may arise from lensing by a protocluster or filament at z ∼ 0.75 where we find an overabundance of massive lens galaxies. We recommend a weak-lensing search for overdensities in “blank” deep fields with the James Webb Space Telescope and the Roman Space Telescope.